Spiritual Assessment Based on Matthew 22:37-40: Faith Integration, Communal Spirituality, and Environmental Stewardship in Indonesian Christian Higher Education - I Made Suardana; Ezra Tari; Oscard Lumban Tobing; Yasinta Waang; Abdiel Enrique Sánchez Revilla (Jurnal Pendidikan Terapan, 2026)
This study addresses the need for a contextual spiritual assessment model in Christian higher education in East Nusa Tenggara, Indonesia, by examining the internalization of the Law of Love (Matthew 22:37–40) in personal spirituality, integration of faith and reason, and environmental stewardship. A descriptive-quantitative survey was conducted with 94 students purposively sampled from four theological institutions in Kupang. Data were analyzed using descriptive statistics, primarily frequency distributions and percentage analysis. The findings revealed that 95.7% of respondents affirmed love as the foundational basis for life decisions (combined "Agree" and "Strongly Agree"). Personal piety was highly endorsed, with 94.7% reporting that daily prayer and Bible reading deepened their relationship with God, and 95.7% indicating that communal worship strengthened their faith. Integration of faith and reason was reflected by 60.6% strongly agreeing that Christian education helped them love God intellectually. Notably, 92.6% affirmed that their faith compels care for the environment (61.7% strongly agree), highlighting an emerging dimension of student spirituality. The study supports the relevance of a Matthew 22:37–40-based assessment model for holistic spiritual formation. However, limitations include reliance on self-report data, a geographically concentrated sample in Kupang, and a cross-sectional design. Future research employing mixed-methods and longitudinal approaches is recommended to validate these preliminary findings and capture behavioral expressions of spiritual formation..